Metastatic Tuberculomas along a Nonfunctioning Ventricular Catheter - Bhople, Laxmikant; Kharosekar, H; Bhide, Anuj; Velho, V (Indian Journal of Neurosurgery, 2021)
A unique case of tubercular meningitis, developing shunt complication, is being reported. We present a pediatric patient with disseminated tubercular granulomas along the ventricular catheter of a nonfunctional ventriculoperitoneal shunt.
Keywords: tuberculomas; shunt tube; ventricular catheter; chemotherapy